2013
DOI: 10.1155/2013/916530
|View full text |Cite
|
Sign up to set email alerts
|

The Age-Related Changes in Cartilage and Osteoarthritis

Abstract: Osteoarthritis (OA) is closely associated with aging, but its underlying mechanism is unclear. Recent publications were reviewed to elucidate the connection between aging and OA. With increasing OA incidence, more senior people are facing heavy financial and social burdens. Age-related OA pathogenesis is not well understood. Recently, it has been realized that age-related changes in other tissues besides articular cartilage may also contribute to OA development. Many factors including senescence-related secret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
129
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(135 citation statements)
references
References 143 publications
(163 reference statements)
4
129
0
2
Order By: Relevance
“…Additionally, with increasing age, the prevalence of cartilage erosion was also found to increase significantly. It has been well documented in many publications that aging has an effect on cartilage morphology and biology, which can cause OA [33,34] .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, with increasing age, the prevalence of cartilage erosion was also found to increase significantly. It has been well documented in many publications that aging has an effect on cartilage morphology and biology, which can cause OA [33,34] .…”
Section: Discussionmentioning
confidence: 99%
“…Cartilage parameters degenerate with advancing age. Due to this degenerative process, there is reduction in cartilage resiliency and hydration, resulting in increased degradation of cartilage, increased roughness of its surface and increased susceptibility to osteoarthritis [3,[25][26][27][28][29][30][31]. Hence, due to proven negative impact of osteoarthritis on muscle strength [23,[33][34][35][36][37], cartilage health showed reduction in muscle strength with advancing grades of clarity and interface.…”
Section: Patients Materials and Methodsmentioning
confidence: 99%
“…Although many studies reported apoptotic chondrocytes in OA cartilage, few have examined apoptosis in cartilage with normal aging, except for one study on rat cartilage. [4] 2. Heredity: Some people have an inherited defect in one of the genes responsible for making cartilage.…”
Section: Chondrocyte Changesmentioning
confidence: 99%
“…Recent research suggests that excess body fat produces chemicals that travel throughout the body and cause joint damage, which would mean obesity, plays a systemic, not just a mechanical, role in osteoarthritis onset. [4] Being only 10 pounds overweight increases the force on the knee by 30-60 pounds with each step. Osteoarthritis is the most common joint disorder with symptoms in the hands, knees, hips, back, and neck.…”
Section: Smokingmentioning
confidence: 99%